The European Union’s Rule of Law Promotion in the Western Balkans: Building a Rule of Law Constituency - Nedim Hogić (Croatian Yearbook of European Law and Policy, 2020)
This paper deals with the failures in the promotion of the rule of law in the six countries of the Western Balkans that are in different stages of their EU accession process. Drawing on concrete examples from more than two decades of rule of law promotion through the enlargement circles, the paper identifies the different evolutionary stages of this undertaking. It finds that the current dominant paradigm of rule of law conditionality concerning the benchmarking of progress in the areas of Chapters 23 and 24 of the acquis fails to tackle state capture as the main structural obstacle to the rule of law in the Western Balkans. The paper proposes that this situation is to be improved by re-imagining rule of law promotion as an effort focused not merely on standards but on building a rule of law constituency. Four different approaches to rule of law promotion that have been less frequently used so far are offered: legal mobilisation, institutional strengthening, the politicisation of anti-corruption, and economic development. The paper concludes with reflections on the realistic reach of the proposed interventions into efforts to promote the rule of law, arguing that while imperfect they remain necessary in order for the project to succeed.